ANALISIS TANDA DALAM IKLAN ROKOK PADA KORAN MANADO POST (TAHUN 2012) (SEBUAH ANALISIS SEMIOTIK) - RONDONUWU, YUNISA CERIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT Semiotics is the study of signs. Sign is the unity of a form of a signifier and signified. Through the combination between the signifier and the signified, we can find meaning in an advertisement. In this research, the writer takes the form of signifier and signified contained in an advertisement in the Manado Post newspaper as the object of research. The purpose of the research is to identify and analyze the signifier and the signified contained in the advertisement in Manado Post newspaper as one sign systems from the semiotics point of view. The aspects of research which are related to the sign systems proposed by Roland Barthes are the signifier, the signified, denotation and connotation. The data about the cigarette advertisements collected from various editions of Manado Post newspaper. All the collected data are analyzed based on Barthes theory of signs, and the method used is descriptive method. The results of this research indicate that each cigarette advertisement in Manado Post newspapers has the same of signified with different signifier. Every cigarette advertisement has the meaning contained in it, that is the denotation and connotation meaning. Diverse connotations, the determination of the meaning or interpretation depends on knowledge, experience, background, and even the emotions of the reader. Keywords: Semiotics, Signifier, Signified, Denotation, Connotation